2014
DOI: 10.1371/journal.pone.0091373
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell-Intrinsic Hepatitis C Virus Expression Leads to B-Cell-Lymphomagenesis and Induction of NF-κB Signalling

Abstract: Hepatitis C virus (HCV) infection leads to the development of hepatic diseases, as well as extrahepatic disorders such as B-cell non-Hodgkin's lymphoma (B-NHL). To reveal the molecular signalling pathways responsible for HCV-associated B-NHL development, we utilised transgenic (Tg) mice that express the full-length HCV genome specifically in B cells and develop non-Hodgkin type B-cell lymphomas (BCLs). The gene expression profiles in B cells from BCL-developing HCV-Tg mice, from BCL-non-developing HCV-Tg mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 72 publications
1
15
0
2
Order By: Relevance
“…The immune selection was performed using ChIP grade NF-κB antibody in combination with Protein G conjugated solid support matrix magnetic beads. This NF-κB antibody has been validated extensively in previous studies to detect NF-κB proteins in Western blots and immunohistochemistry assays 4951 .…”
Section: Experimental and Analytical Methodsmentioning
confidence: 99%
“…The immune selection was performed using ChIP grade NF-κB antibody in combination with Protein G conjugated solid support matrix magnetic beads. This NF-κB antibody has been validated extensively in previous studies to detect NF-κB proteins in Western blots and immunohistochemistry assays 4951 .…”
Section: Experimental and Analytical Methodsmentioning
confidence: 99%
“…NFκB [p65] has been linked to diffuse large B cell lymphoma in many publications. The activation of NF-κB is regulated by two distinct pathways termed the "canonical" and the "non-canonical" NF-κB signalling pathways [5], while the classical NF-κB activation pathway involves dimerization of p50 and p65.…”
Section: Nf-κb [Nuclear Factor Kappa-light-chain-enhancer Of Activatementioning
confidence: 99%
“…The expression of miRNAs is also known to involve NF-κB activation. For example, miR-125a and miR-125b, both of which are often duplicated and/or over expressed in DLBCL, were shown to activate NF-κB by targeting the A20 and NF-κB mediated dysregulation of miRNAs observed in lymphoma [5].…”
Section: Nf-κb [Nuclear Factor Kappa-light-chain-enhancer Of Activatementioning
confidence: 99%
“…However, as the majority of the data derives from in vitro or murine models [Feldmann et al 2006;Sene et al 2007;Ito et al 2011;Marcucci and Mele, 2011], further research is required. Gene expression profiling of lymphoma B cells from HCV-transgenic mice has demonstrated that both canonical and an alternative nuclear factor κB pathway as well as the downregulation of some microRNAs may lead to lymphomagenesis [Kasama et al 2014]. A reduced expression of miR-26b has been found in patients with HCV-positive splenic marginal zone lymphoma (SMZL) [Peveling-Oberhag et al 2012].…”
Section: What Evidence Comes From Epidemiological Studies Linking Nhlmentioning
confidence: 99%